Self-Regulated Learning Practice of Undergraduate Students in Health Professions Programs - Chitra, Ebenezer; Hidayah, Norul; Chandratilake, Madawa; Nadarajah, Vishna Devi (Frontiers in Medicine, 2022)
Background: University students are expected to take charge of their learning without being dependent on teachers. Self-regulated learning (SRL) is the process by which students direct their learning to achieve their set targets and goals in a timely and controlled manner. This study was undertaken to explore the practice of SRL by undergraduate students from different programs in a health science focused university. Method: Thirty-three undergraduate students of five health professions education programs were recruited to take part in focus group discussions to explore their SRL practice. Their responses were subjected to thematic analysis. Result: Students appeared to set goals for academic and personal development. Academic goals, e.g., target GPA or marks, were achieved by following different study techniques, personal management including time management, and creating a conducive learning environment. Personal development such as interpersonal skills, social networking was achieved through socializing and participating in extracurricular activities. The evidence for practicing SRL was observed across all disciplines. However, they appeared to devise and follow their own techniques for achieving goals that they set with regular self-monitoring. Conclusion: Undergraduates of health professions programs follow self-regulated learning to achieve their goals which are related to both academic and personal development. Although there are similarities the SRL processes are individualized and goal dependent.